Non-stomatal inhibition of photosynthesis in are canut palms affected with yellow leaf disease - D. BALASIMHA, P. CHOWDAPPA and (Indian Phytopathology, 2002)
Gas exchange rates in the apparently healthy and yellow leaf diseased (YLD) arecanut palms were studied. Net photosynthetic rate (A) was significantly reduced in the leaves of diseased palms compared to apparently healthy palms, while internal CO2 concentration (C) incre sed. Stomatal conductance (g,) and transpiration rate (E) decreased significantly in. the diseased palms. Significant reductions in Alg, and A/C; ratios were also observed in diseased palms. Similar trend was observed at different times of the day (8.00 to 16.00 h). The results indicate that mesophyll factors were more affected than the stomatal factors in the leaves of diseased palms. Hence, A was reduced more thar, E !e ding to low AlE ratio.